1981
DOI: 10.1302/0301-620x.63b4.7298695
|View full text |Cite
|
Sign up to set email alerts
|

An experimental method for investigating load distribution in the cadaveric human hip

Abstract: A method for direct measurement of the local pressures in the acetabular cartilage is described. Pressure transducers were introduced into the subchondral bone and positioned there in contrast with the cartilage: the transducers were calibrated in situ. Twelve cadaveric hips were prepared in this way and the pressures were measured with the joint loaded in flexion, extension, abduction, adduction, and in lateral and medial rotation. The highest pressures were recorded in the anterior and posterior segments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…During the stance phase, peak values of 5-10 MPa have been determined using Fuji film (Miyanaga et al 1984;Afoke et al 1987), pressure transducers (Day et al 1975, Mizrahi et al 1981Brown and Shaw 1983;Adams and Swanson 1985), pressure sensitive endoprostheses Mann 1979, Rushfeldt et al 1981;Hodge et al 1989;Macirowski et al 1994) and finite element analysis (Brown and Di Giogia 1984;Carter et al 1987;Dalstra and Huiskes 1995). As in our study, other investigators found important variation of the distribution of hip joint pressure between individuals.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…During the stance phase, peak values of 5-10 MPa have been determined using Fuji film (Miyanaga et al 1984;Afoke et al 1987), pressure transducers (Day et al 1975, Mizrahi et al 1981Brown and Shaw 1983;Adams and Swanson 1985), pressure sensitive endoprostheses Mann 1979, Rushfeldt et al 1981;Hodge et al 1989;Macirowski et al 1994) and finite element analysis (Brown and Di Giogia 1984;Carter et al 1987;Dalstra and Huiskes 1995). As in our study, other investigators found important variation of the distribution of hip joint pressure between individuals.…”
Section: Methodssupporting
confidence: 68%
“…As in our study, other investigators found important variation of the distribution of hip joint pressure between individuals. Brown and Shaw (1983) reported pressure maxima in the acetabular roof, but Day et al (1975), Mizrahi et al (1981), Miyanga et al (1984 and Afoke et al (1987) found this stress pattern only in some of their specimens, and in others a bicentric, ventro-dorsal distribution of contact stress. This agrees well with the two types of contact and pressure present in our study.…”
Section: Methodsmentioning
confidence: 95%
“…10,20 The available experimental evidence indicates that normal activities of daily living, like walking, cause peak hip articular surface contact stresses in the range of 4 to 9 N per mm 2 (MPa), 1,[6][7][8]43,74,75 and that these levels of contact stress do not cause visible injury in normal joints. The mean contact stresses generated by normal daily activities are considerably less (in the range of 1 to 3 MPa).…”
Section: Tolerance Of Articular Cartilage For Mechanical Loadingmentioning
confidence: 99%
“…102 This latter observation supports the concept that age increases the vulnerability of articular cartilage to the development of degenerative changes, possibly because of loss of the ability of chondrocytes to maintain and restore the articular surface. [66][67][68][69][70][71][72][73][74][75][76][77] The age-related decline in chondrocyte function, a phenomena referred to as cell senescence, 66,68,70 may be accelerated by joint injuries and residual joint instability following injury.…”
Section: Factors That Increase the Risk Of Joint Injury And Degenerationmentioning
confidence: 99%
“…In the current paper, we address the latter issue. Research indicates that the incongruity in the hip joint produces bi-centric pressure distributions on the femoral head rather than individual parabolic pressure distributions (Mizrahi et al, 1981;Afoke et al, 1984Afoke et al, , 1987Hodge et al, 1986;Fischer et al, 1999a, b). This suggests that parabolic pressure distributions are not indicative of true joint loading patterns.…”
Section: Introductionmentioning
confidence: 99%